2008
DOI: 10.4161/cc.7.9.5808
|View full text |Cite
|
Sign up to set email alerts
|

Protein complexes at the microtubule organizing center regulate bipolar spindle assembly

Abstract: Bipolar spindle assembly is essential to genomic stability in dividing cells. Centrosomes or spindle pole bodies duplicated earlier at G 1 /S remain adjacent until triggered at mitotic onset to become bipolar. Pole reorientation is stabilized by microtubule interdigitation but mechanistic details for bipolarity remain incomplete. To investigate the contribution of spindle pole microtubule organizing center (MTOC) proteins in bipolarity, we applied genetic, structural and molecular biochemical analysis along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 81 publications
0
64
0
Order By: Relevance
“…It has also been shown that Pkl1 is functionally related to ␥-tubulin in the microtubule-organizing center (14), which has been thought to contribute to spindle bipolarity. Most recently, direct association of Pkl1 motor domain with ␥-tubulin has been demonstrated (15). These studies suggest that Pkl1 affects the MT organization via direct interactions with both spindle pole and microtubule-organizing center complexes to regulate spindle bipolarity.…”
mentioning
confidence: 85%
“…It has also been shown that Pkl1 is functionally related to ␥-tubulin in the microtubule-organizing center (14), which has been thought to contribute to spindle bipolarity. Most recently, direct association of Pkl1 motor domain with ␥-tubulin has been demonstrated (15). These studies suggest that Pkl1 affects the MT organization via direct interactions with both spindle pole and microtubule-organizing center complexes to regulate spindle bipolarity.…”
mentioning
confidence: 85%
“…We have used biophysical modeling and quantification of spindle assembly in a cell type that is both relatively simple and amenable to experimental modification, the fission yeast Schizosaccharomyces pombe. This organism has previously been studied in enough detail to allow formulation of a realistic model (78,79); it is small enough that detailed three-dimensional simulations are computationally tractable (80); it is amenable to the genetic manipulation and quantitative experiments needed to parameterize the model (5,6,11,19,20,22,(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98); and the cell contains only three chromosomes whose separate motions can be imaged. Unlike the situation in budding yeast, the mitotic spindle of S. pombe shows important similarities to that of metazoans: Spindle assembly begins in mitotic prophase, and kinetochores attach multiple MTs.…”
Section: Introductionmentioning
confidence: 99%
“…How GCP2 interacts with ctubulin in comparison to Alp4 might also affect its ability to exchange within the complex or be maintained there. The alp4-1891 mutation that lies in the N-terminal domain of Alp4 is suppressed by a mutation in c-tubulin, gtb1-PL302 (Paluh et al, 2000;Tange et al, 2004) that has been shown to result in enhanced binding of Alp4 to c-tubulin (Rodriguez et al, 2008). This means that changes to the N-terminus of Alp4/GCP2 proteins can affect the distal c-tubulin interaction by the Cterminus of these proteins.…”
Section: Discussionmentioning
confidence: 96%